Pengaruh Variasi Konsentrasi Ekstrak Buah Mahkota Dewa (Phaleria macrocarpa) Terhadap Stabilitas Fisik Sediaan Krim - Nur Ain Thomas; Robert Tungadi; Yuni Sarah Manoppo; Dizky Ramadani Putri Papeo; Andi Makkulawu (Jurusan Farmasi Universitas Negeri Gorontalo, 2022)
God's crown is one of the plants with various components with flavonoid as one of these components, which is an abundant plant metabolite component in nature that significantly functions for the plant's growth and antioxidants. This study aimed to examine The Concentration Variation Effect of 70% Ethanol Extract from God's Crown (Phaleria Macrocarpa) Towards The Physical Stability of Cream Preparations by variating the extract concentration. The formula concentration on the extract consists of FI (1%), FII (3%), FIII (5%), by stearic acid, paraffin liquid, alcohol cetyl, paraben propyl for the oil phase, aquadest, triethanolamine (TEA), and methylparaben for the water phase. Further evaluations include organoleptic test (smell, color, texture), pH test, homogeneity test, viscosity test, distribution test, and adhesion test. Each evaluation result found changes as intended by the research purpose, which is the effect of the extract's concentration variation on the physical stability of the cream preparations.